TRACTION POWER TEST OF RAIL BUS 620 M - Bodnar, B. Ye.; Halin, L. F.; Hilievich, O. I.; Varfolomeiev, V. U.; Bobyr, D. V.; Ochkasov, O. B.; Shepotenko, O. P.; Yevdomakha, H. V. (Science and Transport Progress, 2007)
The authors have proposed a method of traction & power tests of a rail bus. The actual test has been conducted in accordance with the developed method. The results of the test are described in the article.